Hereditary Multiple Exostoses Complicated By Common Peroneal Nerve Palsy - Rashid, MA; Moonmoon, TH; Haque, Z; Khan, EH; Nessa, J (Journal of Shaheed Suhrawardy Medical College, 2012)
Hereditary multiple exostoses is an autosomal dominant skeletal disorder. It is characterized by multiple bony prominences and skeletal deformities. It can lead to a series of complications including deformity of the joint, fractures through the tumor pedicle, mechanical block of nearby joints, nerve compression and malignant change. In this case it has been described a rare case of a seventeen-year old male patient with a history of hereditary multiple exostoses presented with foot drop. The management and Physiatric approach are discussed. DOI: http://dx.doi.org/10.3329/jssmc.v4i1.12001 J Shaheed Suhrawardy Med Coll, 2012;4(1):32-34